Multi-Subject Remote Heart Sound Monitoring Using mmWave MIMO RADAR - Isabella Lenz; Yu Rong; Adarsh A. Venkataramani; Daniel W. Bliss (IEEE Journal of Microwaves, 2025)
This work presents a novel non-contact heart sound monitoring approach using millimeter-wave RADAR technology. The proposed system enables simultaneous heart sound acquisition from multiple subjects, offering a contactless and efficient alternative to traditional stethoscopes, which are limited by the need for direct contact and the inability to monitor multiple subjects concurrently. The RADAR-based heart sound system detects surface skin vibrations induced by the heart's mechanical motions through the chest cavity. It translates these mechanical displacements into time-frequency signals for heart sound analysis. The system employs a Frequency-Modulated Continuous-Wave RADAR with optimized parameters for heart sound recording. A complete RADAR signal processing chain is developed, incorporating automatic subject detection and localization using temporal features, spatial beamforming to separate signals from multiple subjects, and heart sound signal extraction. Experimental results demonstrate the system's capability to capture distinct heart sound signatures from up to three subjects simultaneously, with heart rates matching those obtained from reference digital stethoscopes. These findings highlight the potential of millimeter-wave RADAR technology for advanced biomedical sensing applications, enabling remote and simultaneous monitoring of multiple individuals in clinical and non-clinical environments.